Overall Equipment Effectiveness Evaluation of Maintenance Strategies for Rented Equipment - Ade Supriatna; Moses Laksono Singgih; Erwin Widodo; Nani Kurniati (International Journal of Technology, 2020)
Equipment performance is very important in the production process. Equipment performance can be determined by overall equipment effectiveness performance (OEE) and maintenance strategies. This study encourages the use of OEE, in addition to the estimated total maintenance costs, of rental equipment as a consideration in determining optimal maintenance strategies. Meanwhile, the proposed maintenance strategies are corrective maintenance (CM) and a combination of CM with preventive maintenance (PM). The aim of this study was to obtain a maintenance strategy that would minimize the estimated total maintenance costs and increase OEE. Mathematical models of estimated total maintenance costs are developed based on maintenance strategies generated by each maintenance combination. The results of this study showed that when a rental period increases by two years, a combination of CM and PM strategies will cause maintenance costs to increase by 37.54%. Meanwhile, if the lessor only does CM, the increase will be greater (i.e., 55.12%). Comparison of the two strategies revealed that the combination of PM with CM is more efficient than CM alone. Further, OEE experienced an average decline of 3.7% despite the maintenance strategy.